Gold nanoparticles supported on high roughness solid Al2O3 (Superficies y Vacío, 2014)
Conventionally catalytic converters are made of ceramic monoliths as active phase support, because they have high surface area, however on the other side, they are very brittle. Thinking about this problem, one task of this work consists in obtaining a metallic monolith, with suitable roughness for catalytic applications; as well as to deposit on it, Aunanoparticles by plasma discharge, a nonconventional method. In this way, alumina whiskers were grown on FeCrAl alloy by thermomechanical processes, and its surface roughness was quantified by fractal dimension, namely 2.59, for 24 h growth at 900 °C. Grazing X-Ray Diffraction reveals the presence of ? and ? alumina phases making up the 4-5 ?m thickness layer measured in cross-section by SEM, moreover, the X-Ray elements mapping highlights only Al and O on the layer. The Au-nanoparticles deposition on the rough alumina layer was controlled by EBSD-EDXS and for statistical size distribution it was employed an STEM. The average nanoparticle size was of 3.2 nm with a spread of +/- 1 nm and a near 50 % occupancy, this without significant coalescence. As conclusion, peculiar characteristics of a catalytic support were achieved on a metallic substrate and by first time, fractal dimension, as a rigorous mathematical method, was introduced to quantify the substrate surface roughness. The small size and the narrow size distribution of the Au-nanoparticles deposited by plasma, as well as their high dispersion on the alumina grown, overcome the results obtained by conventional methods and promise good catalytic applications.